2016
DOI: 10.1002/acn3.338
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐synuclein RT‐QuIC in the CSF of patients with alpha‐synucleinopathies

Abstract: We have developed a novel real‐time quaking‐induced conversion RT‐QuIC‐based assay to detect alpha‐synuclein aggregation in brain and cerebrospinal fluid from dementia with Lewy bodies and Parkinson's disease patients. This assay can detect alpha‐synuclein aggregation in Dementia with Lewy bodies and Parkinson's disease cerebrospinal fluid with sensitivities of 92% and 95%, respectively, and with an overall specificity of 100% when compared to Alzheimer and control cerebrospinal fluid. Patients with neuropatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
312
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(321 citation statements)
references
References 20 publications
8
312
0
1
Order By: Relevance
“…There are reports of increased CSF concentrations of α-synuclein oligomers in CSF of PD patients [132, 233, 364], and recent publications on sensitive assays that appear to detect the minute amounts of putative seeds of α-synuclein oligomers in CSF [86, 325]. …”
Section: α-Synuclein Pathologymentioning
confidence: 99%
“…There are reports of increased CSF concentrations of α-synuclein oligomers in CSF of PD patients [132, 233, 364], and recent publications on sensitive assays that appear to detect the minute amounts of putative seeds of α-synuclein oligomers in CSF [86, 325]. …”
Section: α-Synuclein Pathologymentioning
confidence: 99%
“…Importantly, because ThT affects the Raman signal, 48 all RT-QuIC reactions were prepared without adding ThT. Indeed, it has been recently demonstrated by different groups 43,49,50 that PD-derived α-synuclein possesses the ability to amplify recombinant α-synuclein when tested by RT-QuIC. Moreover, morphological studies conducted by AFM and TEM showed that DLB-seeded reactions may generate rod-shaped amyloid-fibrils of different sizes differing from other α-synuclein aggregates and exhibiting a more circular and compact appearance.…”
Section: Seeding Variability Of α-Synuclein and Potential Strain Diffmentioning
confidence: 99%
“…The QuIC paradigm has recently been applied to α-synuclein (Fairfoul et al 2016; Hughson et al 2016). One implementation of the assay demonstrated sufficient sensitivity to detect seeding from the cerebrospinal fluid of patients with PD or DLB (Fairfoul et al 2016).…”
Section: Bioassays For Non-prp Prionsmentioning
confidence: 99%
“…One implementation of the assay demonstrated sufficient sensitivity to detect seeding from the cerebrospinal fluid of patients with PD or DLB (Fairfoul et al 2016). Additionally, the QuIC assay has also been applied to measuring the seeding of tau prions (Hughson et al 2016).…”
Section: Bioassays For Non-prp Prionsmentioning
confidence: 99%